MicroRNA-7–regulated TLR9 signaling–enhanced growth and metastatic potential of human lung cancer cells by altering the phosphoinositide-3-kinase, regulatory subunit 3/Akt pathway - Xu, Lin (The American Society for Cell Biology, 2013)
Recent evidence shows that microRNAs (miRNAs) contribute to the biological effects of Toll-like receptor (TLR) signaling on various cells. Our previous data showed that TLR9 signaling could enhance the growth and metastatic potential of human lung cancer cells. However, the potential role of miRNAs in the effects of TLR9 signaling on tumor biology remains unknown. In this paper, we first report that TLR9 signaling could reduce intrinsic miR-7 expression in human lung cancer cells. Furthermore, overexpression of miR-7 can significantly inhibit TLR9 signaling–enhanced growth and metastatic potential of lung cancer cells in vitro and in vivo. Notably, we identify phosphoinositide-3-kinase, regulatory subunit 3 (PIK3R3) as a novel target molecule of miR-7 in lung cancer cells by Western blotting and luciferase report assay. Further study shows that miR-7 inhibits the effects of TLR9 signaling on lung cancer cells through regulation of the PIK3R3/Akt pathway. These data suggest that miR-7 could act as a fine-tuner in regulating the biological effects of TLR9 signaling on human lung cancer cells, which might be helpful to the understanding of the potential role of miRNAs in TLR signaling effects on tumor biology.